The role of confidence in world-class sport performance - Hays, K.; Thomas, O.; Maynard, I.; Bawden, M. (Journal of Sports Sciences, 2009)
In this study, we examined the role of confidence in relation to the cognitive, affective, and behavioural responses it elicits, and identified the factors responsible for debilitating confidence within the organizational subculture of world-class sport. Using Vealey's (2001) integrative model of sport confidence as a broad conceptual base, 14 athletes (7 males, 7 females) were interviewed in response to the research aims. Analysis indicated that high sport confidence facilitated performance through its positive effect on athletes' thoughts, feelings, and behaviours. However, the athletes participating in this study were susceptible to factors that served to debilitate their confidence. These factors appeared to be associated with the sources from which they derived their confidence and influenced to some extent by gender. Thus, the focus of interventions designed to enhance sport confidence must reflect the individual needs of the athlete, and might involve identifying an athlete's sources and types of confidence, and ensuring that these are intact during competition preparation phases.